Transcription factor MAFB controls type I and II interferon response-mediated host immunity in Mycobacterium tuberculosis-infected macrophages - Hikichi, Haruka; Seto, Shintaro; Wakabayashi, Keiko; Hijikata, Minako; Keicho, Naoto (Frontiers in Microbiology, 2022)
MAFB, v-maf avian musculoaponeurotic fibrosarcoma oncogene homolog B, has been identified as a candidate gene for early tuberculosis (TB) onset in Thai and Japanese populations. Here, we investigated the genome-wide transcriptional profiles of MAFB-knockdown (KD) macrophages infected with Mycobacterium tuberculosis (Mtb) to highlight the potential role of MAFB in host immunity against TB. Gene expression analysis revealed impaired type I and type II interferon (IFN) responses and enhanced oxidative phosphorylation in MAFB-KD macrophages infected with Mtb. The expression of inflammatory chemokines, including IFN-γ-inducible genes, was confirmed to be significantly reduced by knockdown of MAFB during Mtb infection. A similar effect of MAFB knockdown on type I and type II IFN responses and oxidative phosphorylation was also observed when Mtb-infected macrophages were activated by IFN-γ. Taken together, our results demonstrate that MAFB is involved in the immune response and metabolism in Mtb-infected macrophages, providing new insight into MAFB as a candidate gene to guide further study to control TB.